Keanekaragaman Hama Pascapanen pada Komoditas Buah Tropis di Pasar Duman, Lombok Barat - Amrul Jihadi; Hari Aditia Pratama, Muhammad; Aulia Rizkika, Gardena (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
This study aims to identify post-harvest fruit pests at Duman Market, West Lombok. The research was conducted at Duman Market, Lingsar Subdistrict, West Lombok Regency, West Nusa Tenggara, using a survey method through direct observation of infested fruits. Ten fruit commodities showing pest infestation symptoms were examined, with parameters including pest types and associated symptoms. The results revealed three pest species attacking fruits at Duman Market, namely Noorda albizonalis, Bactrocera spp., and Tirathaba ruptilinea. These findings highlight the importance of post-harvest pest management in maintaining fruit quality and minimizing economic losses, particularly in traditional markets where diverse fruit commodities are traded. The study also provides baseline data for future research and pest control strategies, supporting efforts to strengthen local agribusiness and improve the competitiveness of Indonesian tropical fruits in domestic and international markets.